2003
DOI: 10.1063/1.1611175
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid quantum chemical studies for the methanol formation reaction assisted by the proton transfer mechanism in supercritical water: CH3Cl+nH2O→CH3OH+HCl+(n−1)H2O

Abstract: A multilayered-representation quantum mechanical/molecular mechanics study of the SN2 reaction of CH3Br + OH− in aqueous solution A general methodology for quantum modeling of free-energy profile of reactions in solution: An application to the Menshutkin NH 3 +CH 3 Cl reaction in water

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 52 publications
0
5
0
1
Order By: Relevance
“…A QM/MM simulation has been performed for chloromethane hydrolysis is supercritical water . The temperature (600 K) and density (0.33 g cm −3 ) used in this study are completely from those in this work, and KIEs were not reported.…”
Section: Resultsmentioning
confidence: 99%
“…A QM/MM simulation has been performed for chloromethane hydrolysis is supercritical water . The temperature (600 K) and density (0.33 g cm −3 ) used in this study are completely from those in this work, and KIEs were not reported.…”
Section: Resultsmentioning
confidence: 99%
“…Elde edilen bu veriler MOPAC2012 programına aktarılarak hesaplama işlemi tamamlanmıştır. MOPAC2012 paket programı içerisinde yer alan PM7 hesaplama yöntemi ile hesaplamalar sulu (ɛ=78,4) [21] fazda ve kan (ɛ=58) [22] fazında T=298K ve T=310K'de yapılmıştır [23]. Hesaplama sonuçlarından üçlü ilaç moleküllerin entalpi (H), oluşum ısıları (Hf) ve entropi (S) değerleri okunmuştur.…”
Section: 1hesaplamada Kullanılan İlaç Molekülleriunclassified
“…The electronic structures of the QM subsystem have been determined by utilizing our original code based on the KS‐DFT 38–44. One of the notable features of our code is that the one‐electron wave functions in the QM subsystem are represented by the real‐space grids 45–47.…”
Section: Computational Detailsmentioning
confidence: 99%